Effect of carbon dioxide-enrichment on tobacco - Awang, Muhamad; A. Halim, Ridzwan (Malaysian Society of Plant Physiology, 1990)
Three-wk old seedlings of tobacco variety Bell-W3 and Bell-B were grown in growth chambers under sunlight and subjected to 3 levels of ambient CO2 concentrations: 300-315 (low), 350-400 (medium) and 600-700 (high) umol mol-1.Weekly measurements of rates of photosynthesis, respiration, transpiration, diffusive resistance and chlorophyll content were taken for 5 wks after which plants were harvested for dry matter yield estimations. Photosynthetic and respiratory rates showed a trend for a quadratic increase with increasing CO2 levels. Variety Bell-W3 had a 27% greater rate of photosynthesis and 12% greater chlorophyll content than variety Bell-B. Variety Bell-W3 also showed a 50% increase in total yield at the high CO2 compared to the medium and low CO2 treatments. No differences in yield was obtained for variety Bell-B. The differences in response between the two varieties may be associated with their inherent photosynthetic capacity.